Increasing brain-computer interface media depictions: pressing ethical concerns. Issue 3 (3rd July 2019) - Gilbert, F; Pham, C; Viaña, Jnm; Gillam, W.
ABSTRACT: This article explores how brain-computer interfaces (BCI) are depicted in the English-speaking media, especially by news outlets. We use the FACTICA database to analyze depictions of BCIs from the first time the term appeared in the media (1993) up until 31 December 2017. We found a sample of over 4064 articles on BCIs. Results indicate that 76.91% of articles portrayed BCI positively, including 25.27% that were overly positive, while 26.64 % of the total articles contain claims about BCI-enabled enhancement. In contrast, 1.6% of articles had a negative tone and only 2.7% of articles flag issues explicitly related to ethical concerns surrounding BCI technology. We propose: 1) A proactive effort by the scientific community to push-out to the media stories focused on the limits and actual capabilities of BCIs, separating science from science fiction; 2) More influence should be brought to bear on the technological risks and process of informed consent.